Pengaruh Asal Negara, Kewajaran Harga, Layanan Purna Jual Terhadap Niat Beli Pada Laptop Lenovo - Resva June Silviana; Arif Rachman Putra (Journal of Trends Economics and Accounting Research, 2022)
The development of technology in the world is growing rapidly and has become a daily necessity, both in terms of science, technology and information. With the modification of all fields, this can overcome the problem of zones and time. Information technology supporting tools will fulfill the need for knowledge and information, especially for students and workers. The purpose of this research is to find out significantly the country of origin, fairness of prices and after sales service for the purchase of Lenovo Laptops. This research is a quantitative research method. This study uses a questionnaire information survey and then collected from the respondents. The population in this study are Lenovo laptop users. The researcher used 100 respondents as the research sample. This study proves that the country of origin has a significant effect on purchase intention on Lenovo laptops. In addition to the country of origin, the reasonableness of the price also has a significant effect on purchase intentions on Lenovo laptops, and after-sales service also significantly influences purchase intentions on Lenovo laptops